Mechanism of Fluconazole Resistance in Candida albicans Biofilms: Phase-Specific Role of Efflux Pumps and Membrane Sterols - Mukherjee, Pranab K. (American Society for Microbiology, 2003)
Candida albicans biofilms are formed through three distinct developmental phases and are associated with high fluconazole (FLU) resistance. In the present study, we used a set of isogenic Candida strains lacking one or more of the drug efflux pumps Cdr1p, Cdr2p, and Mdr1p to determine their role in FLU resistance of biofilms. Additionally, variation in sterol profile as a possible mechanism of drug resistance was investigated. Our results indicate that parent and mutant strains formed similar biofilms. However, biofilms formed by double and triple mutants were more susceptible to FLU at 6 h (MIC = 64 and 16 μg/ml, respectively) than the wild-type strain (MIC > 256 μg/ml). At later time points (12 and 48 h), all the strains became resistant to this azole (MIC ≥ 256 μg/ml), indicating lack of involvement of efflux pumps in resistance at late stages of biofilm formation. Northern blot analyses revealed that Candida biofilms expressed CDR and MDR1 genes in all the developmental phases, while planktonic cells expressed these genes only at the 12- and 48-h time points. Functionality of efflux pumps was assayed by rhodamine (Rh123) efflux assays, which revealed significant differences in Rh123 retention between biofilm and planktonic cells at the early phase (P = 0.0006) but not at later stages (12 and 48 h). Sterol analyses showed that ergosterol levels were significantly decreased (P < 0.001) at intermediate and mature phases, compared to those in early-phase biofilms. These studies suggest that multicomponent, phase-specific mechanisms are operative in antifungal resistance of fungal biofilms.